Microgravity changes at the Laguna del Maule volcanic field: Magma‐induced stress changes facilitate mass addition. Issue 4 (22nd April 2017) - Miller, C. A.; Le Mével, H.; Currenti, G.; Williams‐Jones, G.; Tikoff, B.
Abstract : Time‐dependent, or 4‐D, microgravity changes observed at the Laguna del Maule volcanic field, Chile, since 2013, indicate significant (1.5 × 10 11 kg) ongoing mass injection. Mass injection is focused along the Troncoso fault, and subparallel structures beneath the lake at 1.5–2 km depth, and is best modeled by a vertical rectangular prism source. The low‐density change (156 to 307 kg/m 3 ) and limited depth extent suggest a mechanism of hydrothermal fluid intrusion into existing voids, or voids created by the substantial uplift, rather than deeper‐sourced dike intrusion of rhyolite or basalt magma. Although the gravity changes are broadly spatially coincident with ongoing surface deformation, existing models that explain the deformation are deeper sourced and cannot explain the gravity changes. To account for this discrepancy and the correspondence in time of the deformation and gravity changes, we explore a coupled magmatectonic interaction mechanism that allows for shallow mass addition, facilitated by deeper magma injection. Computing the strain, and mean, normal, and Coulomb stress changes on northeast trending faults, caused by the opening of a sill at 5 km depth, shows an increase in strain and mean and normal stresses along these faults, coincident with the areas of mass addition. Seismic swarms in mid‐2012 to the west and southwest of the mass intrusion area may be responsible for dynamically increasing permeability on the Troncoso fault, promoting influx of hydrothermal fluids, which in turn causes larger gravity changes in the 2013 to 2014 interval, compared to the subsequent intervals. Plain Language Summary: Movement of liquid below the Earth's surface occurs in response to a variety of volcanic or tectonic processes and may result in changes that are measurable on the surface of the Earth. Understanding what causes these changes helps inform on the state of a volcanic system and how close it is to eruption. We present results of measurements showing changes in the Earth's gravity at the Laguna del Maule volcanic field, Chile. These measurements show small increases in gravity around the lake since 2013, coincident to where the ground is being uplifted by deep magma intrusion. Using computer simulations, we find that the location of the gravity changes is at 1.5 to 2 km below the Earth's surface and is likely caused by the intrusion of water into an area of rock that is fractured by land movement. Flow of water into this fractured rock is facilitated by pressure exerted by deeper intruding magma, opening up the rock above and allowing water to flow into the space created. Our study provides important constraints on processes that are otherwise undetectable and allow us to better understand the dynamics of an active magma system. Key Points: First results of microgravity increases measured at Laguna del Maule from 2013 to 2016 presented Mass addition models indicate hydrothermal fluid intrusion along faults at 1.5 to 2 km depth Deeper magma intrusion changes stress and strain around faults, increasing permeability and facilitating fluid migration